Why should safety and security civilization (SSC) be a new concept of safety and security science? - Chao Wu (Emergency Management Science and Technology, 2023)
In order to increase the number of general concepts of safety and security science which can be used to represent the comprehensive safety and security level of a system, a compound word of safety and security civilization (SSC) is proposed, based on the connotation and attributes of words of civilization, safety and security. Then, the narrow and generalized definitions and their connotations of SSC are given respectively. Further analysis shows that properties of SSC have implications of comprehensiveness, generality, abstractness and progressiveness. On this basis, various classifications of SSC are made from different perspectives and dimensions, and the similarities and differences between SSC and safety culture are compared. SSC is an advanced part of generalized safety culture and can be used to guide the construction of safety culture. The research shows that the new concept of SSC can be widely used to express the whole safety and security level at a certain time and space, and has important value in practical applications.